2014
DOI: 10.7196/sajbl.330
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant, dead, and on a ventilator: A few thoughts in response to Prof McQuoid-Mason

Abstract: Advances made by medical science are able to extend human life, sometimes by highly technical means such as life-support systems. Often these procedures prove life-saving, and the patient recovers fully; at other times, however, life-extending treatment is futile, such as when the patient is declared brain dead. Advances in reproductive technologies, similarly, have been able bring hope by treating and curing infertility. This article responds to an article by Professor McQuoid-Mason entitled 'Terminating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Eğer fetüsün yaşayabilir olduğu tıbbi kanısı var ise, ölü anneden sezaryen ile doğum yaptırılır. Eğer hekimde bu kanı oluşmadı ise fetüs anne karnında ölüme terk edilir (10). Yaşabilirlik ile ilgili iki farklı tanım olduğunu söylenebilir.…”
Section: Fetüsün Yaşayabi̇li̇rli̇ği̇ üZeri̇neunclassified
“…Eğer fetüsün yaşayabilir olduğu tıbbi kanısı var ise, ölü anneden sezaryen ile doğum yaptırılır. Eğer hekimde bu kanı oluşmadı ise fetüs anne karnında ölüme terk edilir (10). Yaşabilirlik ile ilgili iki farklı tanım olduğunu söylenebilir.…”
Section: Fetüsün Yaşayabi̇li̇rli̇ği̇ üZeri̇neunclassified
“…It has been suggested that a South African (SA) court would have come to a similar decision but for different reasons. [2] A recent article commenting on the Munoz case, [3] begs the question of whether if the pregnant woman had been in a persistent vegetative state (PVS) the courts in South Africa would have reached the same conclusion on the basis that she had expressed her wish not to be kept alive in an advance directive, and that keeping her alive against her wishes would have been a violation of her constitutional rights to equality, dignity, privacy and bodily integrity. [3] To answer this question it is necessary to consider the following in the context of SA law:…”
mentioning
confidence: 99%